2015
DOI: 10.1007/s00429-015-1064-1
|View full text |Cite
|
Sign up to set email alerts
|

A unique cellular scaling rule in the avian auditory system

Abstract: Although it is clear that neural structures scale with body size, the mechanisms of this relationship are not well understood. Several recent studies have shown that the relationship between neuron numbers and brain (or brain region) size are not only different across mammalian orders, but also across auditory and visual regions within the same brains. Among birds, similar cellular scaling rules have not been examined in any detail. Here, we examine the scaling of auditory structures in birds and show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…However, social interactions in ruffed grouse are extremely rare and have primarily been inferred from removing males from drumming logs and those logs being occupied by other males within a breeding season (Boag, ; Gullion, ). In cases where we have removed grouse for anatomical studies (Corfield, Harada, et al., 2013; Corfield, Krilow, et al., 2013; Corfield et al., ; Krilow & Iwaniuk, ), the drumming log has remained unoccupied for the rest of the breeding season and Berkeley () found no log turnover across several breeding seasons in the same study area as Gullion (). Given this variation in whether males can displace or replace one another at a drumming log and the general lack of any observable social interactions, if social dominance is responsible for the differential response, it is unclear how dominance status could be assessed in ruffed grouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, social interactions in ruffed grouse are extremely rare and have primarily been inferred from removing males from drumming logs and those logs being occupied by other males within a breeding season (Boag, ; Gullion, ). In cases where we have removed grouse for anatomical studies (Corfield, Harada, et al., 2013; Corfield, Krilow, et al., 2013; Corfield et al., ; Krilow & Iwaniuk, ), the drumming log has remained unoccupied for the rest of the breeding season and Berkeley () found no log turnover across several breeding seasons in the same study area as Gullion (). Given this variation in whether males can displace or replace one another at a drumming log and the general lack of any observable social interactions, if social dominance is responsible for the differential response, it is unclear how dominance status could be assessed in ruffed grouse.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 64 males were provided 109 playbacks from 2012 to 2015. All of the recordings used were from males that were removed from the population for parallel anatomical studies (Corfield, Harada, & Iwaniuk, 2013; Corfield, Krilow, Ligt, & Iwaniuk, 2013; Corfield, Long, Krilow, Wylie, & Iwaniuk, ; Krilow & Iwaniuk, ), so none of these males were exposed to playbacks from themselves. From these, 32 males received a single stimulus playback (pulse rate = 4.981 Hz) and 32 males were provided two playback sessions with two different stimuli: one with a fast drumming rate and another one with a slow rate.…”
Section: Methodsmentioning
confidence: 99%
“…Since animals were not killed to conduct this study, no university ethics approvals were required for this research. Additional data were compiled from the studies of Ebinger and Lohmer (1987) , Boire (1989) , Rehkamper et al (1991) , Alma and Bee De Speroni (1992) , Carezzano and Bee De Speroni (1995) , Fernandez et al (1997) , Pistone et al (2002) , Mehlhorn et al (2010) , Corfield et al (2011 , 2012b , 2014 , 2015 ), Gsell (2012) , Cunningham et al (2013) , and Gutierrez-Ibanez et al (2014) . Whole brain, telencephalon, and OBs sizes are included in Supplemental Table S1 , which also includes the source, common names, and order for each species.…”
Section: Methodsmentioning
confidence: 99%
“…Together with phylogeny, ecology, and behavior, the rules that govern the scaling of OBs with brain/body size are also likely to be influencing the relative sizes of OBs. Indeed, the patterns of neural scaling can be an important determinant of the size of specific brain regions ( Herculano-Houzel, 2009 ; Ribeiro et al, 2014 ; Corfield et al, 2015 ). Therefore, it is clear that many factors, including, but not limited to, phylogeny, ecology/behavior, and neural scaling patterns are driving the diversity in OB sizes in birds.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the hormone levels were influenced by the body size, gender, and were associated with the species of Galliformes (e.g. Jankowski et al 2014;Corfield et al 2016). Some evidence also showed that maternal hormones were a good pathway to influence offspring development.…”
Section: Physiology and Biochemistrymentioning
confidence: 99%